2007
DOI: 10.1182/blood-2006-08-039255
|View full text |Cite
|
Sign up to set email alerts
|

Defining the in vivo function of Siglec-F, a CD33-related Siglec expressed on mouse eosinophils

Abstract: CD33-related Siglecs (CD33rSiglecs) are a family of sialic acid–recognizing lectins on immune cells whose biologic functions are unknown. We studied in vivo functions of Siglec-F, the CD33rSiglec expressed on mouse eosinophils, which are prominent in allergic processes. Induction of allergic lung inflammation in mice caused up-regulation of Siglec-F on blood and bone marrow eosinophils, accompanied by newly induced expression on some CD4+ cells, as well as quantitative up-regulation of endogenous Siglec-F liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
241
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(256 citation statements)
references
References 43 publications
14
241
1
Order By: Relevance
“…Siglec-F is a sialic acid-recognizing lectin present on the surface of mouse eosinophils and is upregulated during allergic lung inflammation (40). Other cells, including pulmonary macrophages, may also express Siglec-F but are successfully excluded by costaining with CD11c, with the CD11c-negative population of Siglec-F-positive lung cells identifying eosinophils (35).…”
Section: Cd4 Depletion In the Lung And Lung-draining Lymph Nodesmentioning
confidence: 99%
“…Siglec-F is a sialic acid-recognizing lectin present on the surface of mouse eosinophils and is upregulated during allergic lung inflammation (40). Other cells, including pulmonary macrophages, may also express Siglec-F but are successfully excluded by costaining with CD11c, with the CD11c-negative population of Siglec-F-positive lung cells identifying eosinophils (35).…”
Section: Cd4 Depletion In the Lung And Lung-draining Lymph Nodesmentioning
confidence: 99%
“…Siglec-F, a recently identified inhibitory receptor on mouse eosinophils and its human functional homologue Siglec-8 have been shown to induce apoptosis when crosslinked in vitro by mAbs (12,13). It remains to be determined whether Siglec-F can act as inhibitory receptor and regulate degranulation of eosinophils.…”
mentioning
confidence: 99%
“…8,9 Furthermore, mice deficient in mouse Siglec-F have exaggerated allergic lung eosinophilic responses. 10 These findings underscore the importance of Siglec-F/8 in eosinophil apoptosis and human eosinophil-mediated disorders like asthma.…”
Section: Introductionmentioning
confidence: 77%
“…3 Of interest, murine Siglec-8 variations and asthma P-S Gao et al studies targeting Siglec-F, the closest functional paralog to Siglec-8, also demonstrated a significant role in regulating the pathogenesis of eosinophil-mediated disorders. [8][9][10] As eosinophils and their many biologically active mediators are associated with allergic diseases and other chronic inflammatory disorders, this suggests that Siglec-8 could be a candidate gene for human eosinophilic disorders like asthma and EE.…”
Section: Discussionmentioning
confidence: 99%